The shariah committee attributes, advising role and the preservation of religion in the Malaysian Islamic financial institution - Mohammed Shah, Sabarina; Hassan, Mohamat Sabri; Mohd Saleh, Norman; Ahmad, Sanep (Halal Products Research Institute, Universiti Putra Malaysia, 2014)
Previous studies had documented evidences which were incoherent of which either focused on the Shariah Committee attributes or the IFI performance based on profitability and corporate social responsibility. Furthermore, these performance measurements are considered inappropriate as it should be based on the achievement of the maqasid al shariah. Hence, this study addresses this gap by examining the effectiveness influenced by Shariah Committee attributes and its involvement in the advising role in achieving maqasid al shariah. It is a process oriented approach through the lens of Islamic Accountability based on the Shariah Governance Framework (SGF) 2011. This study extends the attributes of the Shariah Committee members to include the component of their tawhidic values and the achievement of the maqasid al shariah through their perceptions. Therefore, the quantitative approach through survey was employed whereby the questionnaire, based on three main constructs namely the Shariah Committee attributes, advising role, the maqasid al shariah specifically in preservation of religion, was developed. It was distributed to a total sample of 240 which is subdivided into 113 and 127 of Shariah Committee members and Shariah Personnel in Malaysian IFI, respectively. Subsequently, a cross sectional model is applied for it enables the examination of the existing relationship simultaneously which resulted in the structural path model. The structural path model revealed that there is a significant positive relationship between the Shariah Committee attributes and the maqasid al shariah in preservation of religion. However, it is found that the Shariah Committee advising role do not mediate this relationship. Thus, the implication of this research placed the importance of highly qualified Shariah Committee members and greater involvement in their advising roles in order to achieve the maqasid al shariah in terms of the preservation of religion.